A synergistic model for developing a committed workforce in dynamic organizations - Mubarak Rana Zeeshan, Awang Marinah, (Universiti Pendidikan Sultan Idris, 2017)
A synergistic model for developing a committed workforce in dynamic organizations by Mubarak Rana Zeeshan, Awang Marinah,